2018
DOI: 10.3178/hrl.12.14
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of future flood risk in Asian megacities: a case study of Jakarta

Abstract: The purpose of this research is to assess the future flood risk in rapidly urbanizing cities under climate change. A flood inundation model and a flood damage costs model were employed to project the future flood risk. We employed the combinations of eight global climate models (GCMs) and three representative concentration pathways (RCPs) for precipitation to represent the climate change. Land-use change and land subsidence information were employed to represent the urban development effects. The expected annu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…According to Bricker et al (2014), the reduced capacity of the drainage system generated by trash-clogging flood gates is a factor that causes flooding. Budiyono et al (2016) and Januriyadi et al (2018) reported that climate change in the future would increase flood risk in Jakarta.…”
Section: Introductionmentioning
confidence: 99%
“…According to Bricker et al (2014), the reduced capacity of the drainage system generated by trash-clogging flood gates is a factor that causes flooding. Budiyono et al (2016) and Januriyadi et al (2018) reported that climate change in the future would increase flood risk in Jakarta.…”
Section: Introductionmentioning
confidence: 99%
“…In Can Tho, Vietnam climate change-related changes such as sea-level rise and increased river flow have projected to increase flood risk within the city (Huong and Pathirana 2013). In Jakarta, mean future flood risk is projected to increase by 300-400% (Januriyadi et al 2018). However, climate change and its impacts have received little attention within research focused on FSA identification.…”
Section: Climate Change and Future Adaptationmentioning
confidence: 99%
“…Betweenness centrality (BC) is based on the shortest path between two nodes in the network. It measures how frequently a node lies on the shortest paths among all possible node pairs (Freeman, 1977;Wang et al, 2018). The betweenness centrality of a nodes denotes the fraction of shortest paths which pass through the focal node between all node pairs (Equation Eq.…”
Section: Network Analysismentioning
confidence: 99%